Pengaruh Citra Produk Berdasarkan Analisis Persepsi Konsumen pada Kelompok Usaha Aneka Pangan Kota Sidoarjo - Artaya, I Putu; Kamisutara, Made; Baktiono, R Agus (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2018)
The perception of products in the consumer society can not be separated from the label design, given the first impression that appears when consumers see the product is based on whether or not good label used. This study focuses on a small business group of various food and craft products in Sidoarjo that tend to retain traditional packaging models. The group is a producer of food products and various handicrafts where it is still done and produced simply. Given the advancement of technology and label design so far is increasingly rapidly it is necessary to touch the technological advances in this business group products so that the label design can improve the positive perception of consumers when looking at the product. The tendency of the market so far that the products produced by small business groups are increasingly in demand by the global market, of course, this condition requires care and handling well, especially on the packaging label of its products. To facilitate the analysis of the trigger consumer perceptions in the identification using several factors that interact directly inherent in the resulting product. Through factor analysis approach is expected to know significantly that what factors need to be known and improved so that consumers have a strong interest in all forms of products produced by small business groups. Furthermore, policy and actions can be taken on the improvement of labels on some products that can be used as a superior product for small business actors in Sidoarjo city area. The increase of small-scaled business actors in Sidoarjo city is closely related to the emergence of various small business opportunities within the home industry groups that have the potential to be developed in the future.